Essential requirements for connection of terminal equipment to analogue interfaces of public switched telecommunications networks using either the earth calling, the loop calling, disconnect clearing, the loop calling, guarded clearing or the loop calling, unguarded clearing signalling method. (15th May 1995) - British Standards Institution,
No abstract available